Applications of Intelligent Technologies in Healthcare - Khan, Fazlullah; Jan, Mian Ahmad; Alam, Muhammad; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book covers topics related to medical practices from communications technology point of view. The book provides detailed inside information about the use of health informatics and emerging technologies for the well-being of patients. Each chapter in this book focuses on a specific development in the use of informatics in healthcare. In general, each chapter uses various emerging technologies such as Internet of Things (IoT), Big Data, Cloud computing, Wireless Body Area Networks (WBAN), for various health-related illness, such as tuberculosis, heart diseases, asthma and various epidemic outbreaks. The book is intended both for communications engineers with a healthcare focus and medical researchers. .
Introduction -- Quality Assessment and Classification of heart sounds using PCG signal -- Classification of Normal Heart beats using Spectral and non-spectral features for phonocardiography signals -- Segmentation of Chest Radiographs for Tuberculosis Screening Using Kernel Mapping and Graph Cuts -- Survey Analysis of Automatic Detecting and Grading of Cataract using Different Imaging Modalities -- A privacy risk assessment for the Internet of Things in Healthcare -- Parallel Computation on Large Scale DNA Sequences -- Augmented and Virtual Reality in Mobile Fitness Applications: A Survey -- Cloud-assisted IoT-based smart respiratory monitoring system for asthma patients -- Blood cells counting and segmentation using Image Processing techniques -- SmartAssist- Smartphone Based Drug Compliance for Elderly People and People with Special Needs -- An Overview of OCT Techniques for Detection of Ophthalmic Syndromes -- Fully automated identification of heart sounds for the analysis of cardiovascular pathology -- Modeling and Simulation of Resource constrained Vaccination Strategies and Epidemic outbreaks -- Big Data in Healthcare: A Survey -- Conclusion.
Keywords: Telecommunication; Medical informatics; Health services administration; User interfaces (Computer systems).; Human-computer interaction; Communications Engineering, Networks; Health Informatics; Health Care Management; User Interfaces and Human Computer Interaction